Factors influencing exclusive breastfeeding among Iranian mothers: A longitudinal population-based study - Mohsen Saffari; Amir H. Pakpour; Hui Chen (Tabriz University of Medical Sciences, 2017)
Background: Exclusive breastfeeding (EBF) contributes to the health and survival of the newborns. Many factors influence the EBF behavior. This study aimed to identify the determinant factors in order to improve the practice of EBF among Iranian mothers. Methods: A longitudinal study was carried out in 1445 mothers with newborns in Qazvin city, Iran (September 2015-March 2016). Demographic variables as well as the constructs of theory of planned behavior (TBP) were measured by questionnaires. Bivariate analysis using Pearson and Spearman correlation tests with analysis of variance were used to investigate the associations among the variables. Both hierarchal multiple regression and logistic regression were applied to identify potential determinative factors for the EBF. Results: Nearly, 80% (CI: 77.97-82.63%) of the participants had the intention of EBF. All TPB constructs, moral norms, and self-identity were significantly correlated with each other (r: 0.09- 0.40, P < 0.01). Some demographic variables such as age, income, employment and primiparity were also correlated with the EBF (r: 0.11-0.15, P < 0.05). The constructs of the TPB were able to predict the EBF behavior, which account for 49% of the variance in the predicting factors (df = 8, F = 7.70). The self-identity and moral norms accounted for an additional 15% of the variance (df = 10, F = 3.16). Younger mothers with lower socio-economic status were at higher risk of EBF cessation. The intention has a greater impact on the initiation of EBF than perceived behavioral control (PBC) but not for the maintenance of EBF (OR, 2.88 [CI: 2.38-3.48] & 1.13 [CI:1.03- 1.23] vs. OR, 1.27 [CI:1.15-1.39] & 2.66 [CI: 2.02-3.49]). Conclusion: The interventions to promote knowledge, attitude and behavioral control towards the EBF should be considered especially in the young mothers with low socio-economic status.